Analysis to stationary transmission model of P2P streaming - Cheng-wei WAN; Jiang-xing WU; Ju-long LAN (Tongxin xuebao)
It was proved that the P2P streaming system could be modeled by a queuing chain which was composed by multiple M/M/n queuing system according to the queuing theory.Based on this result,the stationary transmission model of P2P streaming was proposed by the analysis on the peer buffer state variation.The transmission characteristics under different chunk schedule strategies were examined by the model,and the results validated the rationality of the proposed model.Further more,the impact of peer number and buffer size on the transmission characteristic was examined.